Association of Carbapenemase-Producing Enterobacterales Detected in Stream and Clinical Samples - Sung, Gyung-Hye; Kim, Si Hyun; Park, Eun Hee; Hwang, Suk Nam; Kim, Jea-Dong; Kim, Gyu Ri; Kim, Eun-Young; Jeong, Joseph; Kim, Sunjoo; Shin, Jeong Hwan (Frontiers in Microbiology, 2022)
Background The spread of carbapenem-resistant Enterobacterales (CRE) strains has caused treatment failure and is a worldwide threat to public health. However, there are limited reports on the prevalence of carbapenemase-producing Enterobacterales (CPE) in aquatic environments and its association with clinical isolates. This study aimed to investigate the prevalence of CPE in a stream environment and its genetic relationship with clinical isolates in Korea. Methods A total of 4,582 water samples were collected from 94 streams. Multiplex PCR and sequencing were used to detect and identify six carbapenemase genes. Multi-locus sequence typing (MLST) was performed to investigate the genetic relatedness between the environmental strains and clinical isolates. Results A total of 133 CRE strains were isolated from the streams. Klebsiella pneumoniae was the most common CRE (45.9%), followed by Enterobacter cloacae complex (29.3%), Escherichia coli (13.5%), Raoultella ornithinolytica (5.3%), and Citrobacter freundii (2.3%). Ninety (67.7%) isolates carried carbapenemase genes. K. pneumoniae carbapenemase-2 (36.7%) and New Delhi metallo-β-lactamase-5 (32.2%) were the common carbapenemases detected. Sequence type (ST)307 and ST11 K. pneumoniae strains harboring the blaKPC-2 gene were the most prevalent in stream and patient samples. Conclusion CPE was highly prevalent in streams and closely related to the isolates obtained from patients. Therefore, continuous monitoring of stream environments is required to control the spread of carbapenem resistance.